Translation Quality Assessment in Medical Texts from Persian into English on the Basis of Baker's Taxonomy of Grammar and Vocabulary within the Scientific Text Model - Salmani, Bahloul; Janfaza, Elenaz; Janfaza, Sulmaz (Mediterranean Journal of Social Sciences, 2012)
Translation quality assessment is one of the areas that need more attention on the part of the assessor. Since, it needs boththeory of translation on the one hand, and proficiency and competency as a translator, on the other hand, on the part of the translationassessor.Translation within the fields of medical sciences has not got its proper focus of attention. The nature of medical texts demandstransfer of information. However, from vocabulary and grammatical prospects, sometimes great pitfalls are seen. The present study triesto investigate the general knowledge of language in medical texts translation.The present study has applied Baker's (1988) Taxonomy ofgrammar and vocabulary model within the medical texts to show the ability and art of the translator in compare with the translation ofmedicine.